Open-Circuit Fault Diagnosis and Fault Tolerant Operation of Interleaved DC–DC Boost Converters for Homes and Offices - Bento, Fernando (2020)
The use of electronic equipment and other dc-compatible appliances in homes and offices is increasing at a very fast rate, as well as the distributed generation of energy. These two statements will most likely trigger, in a near future, the adoption of district-scale dc grids, connecting dc microgeneration plants and consumers, in an effort to cut the number of conversion steps required to deliver power to dc appliances. DC-DC converters will be fundamental in these systems, allowing the establishment of several voltage levels. The reliability of these converters plays a critical role, ensuring service continuity of the loads connected to them. With the increment of reliability in mind, this paper proposes a simple yet effective open-circuit fault diagnostic method suitable for interleaved dc-dc boost converters, but equally functional for other dc-dc converter topologies. The improvements introduced in this paper greatly simplify the diagnostic action, while making the correct diagnostic of faults independent of the switching duty cycle. Moreover, an alternative reconfiguration scheme is proposed to mitigate the adverse impacts of such faults. To prove the effectiveness of these strategies, a three-phase interleaved boost converter prototype was used in the experiments.